Folate receptor alpha antagonists in preclinical and early stage clinical development for the treatment of epithelial ovarian cancer. (1st December 2016) - Bergamini, Alice; Ferrero, Simone; Leone Roberti Maggiore, Umberto; Scala, Carolina; Pella, Francesca; Vellone, Valerio Gaetano; Petrone, Micaela; Rabaiotti, Emanuela; Cioffi, Raffaella; Candiani, Massimo; Mangili, Giorgia
ABSTRACT: Introduction: The prognosis of patients affected by ovarian cancer has not substantially changed in the last decades and improving survival still remains a challenge. In the promising era of 'personalized therapy' several new biologic therapies are currently being investigated: in this setting, targeting the folate receptor (FR) has been considered a new potential strategy for biologic therapy. Areas covered: The aim of the current review is to summarize, giving a critical overview, promising folate receptor alpha antagonists under preclinical or early clinical development for ovarian cancer. Expert opinion: Two categories of therapeutics are included in this class: FRα targeted mAbs and FRα-binding-ADC (Antibody drug conjugates); both share the interesting possibility of selecting patients via a biomarker which is already available. In the first class, farletuzumab has reached the most advanced stage in clinical evaluation and results of a Phase II randomized trial are awaited to assess its efficacy in a specific patients' setting. MOv18 IgE represents a novel strategy to target FRα expressing cells, which has shown encouraging results in preclinical studies: further evaluation is needed in the clinical setting. IMGN 853 is an innovative FRα-binding ADC under development, with only preliminary results of a Phase I trial available.